What drives hyperammonemic encephalopathy in AED users: monotherapy risks or polypharmacy perils? - Shan, Qing; Wang, Lei; Liu, Xia; Chen, Yan; Li, Bing; Guo, Yuhang; Fu, Qiang; Guo, Jinmin (Frontiers in Pharmacology, 2025)
Background and objectivesHyperammonemic encephalopathy (HE) is a serious side effect linked to sodium valproate (VPA). Recent case studies indicate that newer antiepileptic drugs (AEDs) might also trigger HE, whether used alone or alongside VPA. This study investigated the risk factors of HE linked to 10 AEDs using data from the FDA Adverse Event Reporting System (FAERS), focusing on VPA co-administration effects.MethodsFAERS reports from the first quarter of 2013 to the third quarter of 2024 were examined for ten frequently prescribed antiepileptic drugs (AEDs): VPA, perampanel (PER), phenytoin (PHT), carbamazepine (CBZ), topiramate (TPM), lamotrigine (LTG), levetiracetam (LEV), oxcarbazepine (OXA), clonazepam (CZP), and zonisamide (ZNS). Hepatic event (HE) signals were evaluated using reporting odds ratios (ROR). A multivariate logistic regression analysis was conducted to assess risk factors (age, gender, indication, drug combinations). Particular attention was given to the effects of VPA in combination with LEV, TPM, olanzapine (OLZ), or quetiapine (QTP) on the risk of HE.ResultsA total of 1,456 HE-related events were identified, with 93.06% of these events linked to AEDs. VPA had the highest association with HE (ROR = 122.14, 95% CI: 110.16–135.41), followed by PER, which was independent of VPA (ROR = 52.62). Eight additional AEDs also indicated positive associations, mainly influenced by VPA (such as TPM and LEV). Identified risk factors for HE included age (with a lower risk observed in minors, OR = 0.61, 95% CI [0.50–0.76]) and clinical indication (with a lower risk in psychiatric disorders, OR = 0.74, 95% CI [0.62–0.89]). The combination of VPA+TPM significantly raised the risk of HE (OR = 3.38, 95% CI [2.25–5.06]) without negatively impacting outcomes. Furthermore, combinations of antipsychotic medications with VPA also indicated an increased risk of HE (OLZ+VPA: OR = 1.65, 95% CI [1.18–2.30], QTP+VPA: OR = 1.95, 95% CI [1.39–2.75]).ConclusionThis research underscores the possible danger of HE related to AEDs, with a particular focus on the risks tied to VPA and PER when used alone, as well as VPA in conjunction with TPM, OLZ, or QTP. It emphasizes the need to monitor ammonia levels in patients on AEDs, particularly those on polypharmacy.